2023
DOI: 10.3389/fimmu.2023.1287698
|View full text |Cite
|
Sign up to set email alerts
|

Genetic evidence supporting the causal role of gut microbiota in chronic kidney disease and chronic systemic inflammation in CKD: a bilateral two-sample Mendelian randomization study

Feihong Ren,
Qiubai Jin,
Qi Jin
et al.

Abstract: BackgroundThe association of gut microbiota (GM) and chronic kidney disease (CKD), and the relevancy of GM and chronic systemic inflammation in CKD, were revealed on the basis of researches on gut–kidney axis in previous studies. However, their causal relationships are still unclear.ObjectiveTo uncover the causal relationships between GM and CKD, as well as all known GM from eligible statistics and chronic systemic inflammation in CKD, we performed two-sample Mendelian randomization (MR) analysis.Materials and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Previous studies on the gut microbiome and CKD have primarily utilized animal models ( Vaziri et al, 2013 ), with observations often showing inconsistencies. While there have been reports on the causal relationship between the gut microbiome and CKD ( Li et al, 2023 ; Ren et al, 2023 ), significant variations in the richness and evenness (α-diversity) of bacterial species across different CKD stages have been observed ( Wu et al, 2020 ). CRF represents a more severe stage of kidney pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on the gut microbiome and CKD have primarily utilized animal models ( Vaziri et al, 2013 ), with observations often showing inconsistencies. While there have been reports on the causal relationship between the gut microbiome and CKD ( Li et al, 2023 ; Ren et al, 2023 ), significant variations in the richness and evenness (α-diversity) of bacterial species across different CKD stages have been observed ( Wu et al, 2020 ). CRF represents a more severe stage of kidney pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Lower p -value thresholds (e.g., < 5.0E−08) are commonly employed to ensure robustness of associations, reduce heterogeneity, and enhance the accuracy of the research. However, such stringent criteria might also exclude potentially meaningful associations ( Bottigliengo et al, 2022 ; Chen et al, 2023 ; Liu et al, 2023 ; Ren et al, 2023 ). Our analysis indicated that some associations, previously insignificant, became significant when the p -value threshold was relaxed, underscoring the importance and complexity of p -value selection in research on the relationship between inflammatory proteins and ALS.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, we employed MR analysis, providing a robust framework to systematically investigate the causal relationship between Shigella infection and the gut microbiota. Ren et al, 2023). CRP has been previously recognized as a marker of Shigella infection activity (Khan et al, 1995).…”
Section: Discussionmentioning
confidence: 99%